Technology Proficiency and School Culture as the Influence of Teaching Behavior among Public Elementary School Teacher - Maricris U. Catog (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aimed to determine the technology proficiency and school culture influence of teaching behavior among public elementary school teachers. The study employed a descriptive-correlational research technique which is designed to gather data, ideas, and information. This assesses the levels of technology proficiency, school culture, and teaching behavior of 300 public elementary school teachers. Based on the results, only school culture was the predictor that best predicted the teacher behavior of the public elementary teacher. The results of the findings are discussed in relation to encouraging teachers to improve their technology proficiency and school culture which may affect their behavior where integrating technology to teach and manage school structures may have an impact on engaging relationships with their students.